2008
DOI: 10.1007/s10494-008-9187-6
|View full text |Cite
|
Sign up to set email alerts
|

On Temporal Stability Analysis for Hydromagnetic Flow in a Channel Filled with a Saturated Porous Medium

Abstract: In this paper, a linear stability analysis is presented to trace the time evolution of an infinitesimal, two-dimensional disturbance imposed on the base flow of an electrically conducting fluid in a channel filled with a saturated porous medium under the influence of a transversely imposed magnetic field. An eigenvalue problem is obtained and solved numerically using the Chebyshev collocation spectral method. The critical Reynolds number Re c , the critical wave number α c and the critical wave speed c c are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Postelnicu [5] investigated the combined effects of magnetic fields, thermal-diffusion and diffusion-thermo on heat and mass transfer by natural convection from vertical surfaces in porous media. Other studies on flow and heat transfer in porous media can be found in [6][7][8]. Meanwhile, the current trend of analysing flow and heat transfer is to apply a Second Law (of Thermodynamics) analysis, and its design-related concept of entropy generation minimization (EGM).…”
Section: Introductionmentioning
confidence: 99%
“…Postelnicu [5] investigated the combined effects of magnetic fields, thermal-diffusion and diffusion-thermo on heat and mass transfer by natural convection from vertical surfaces in porous media. Other studies on flow and heat transfer in porous media can be found in [6][7][8]. Meanwhile, the current trend of analysing flow and heat transfer is to apply a Second Law (of Thermodynamics) analysis, and its design-related concept of entropy generation minimization (EGM).…”
Section: Introductionmentioning
confidence: 99%
“…Some attempts have also been made to use nano-technologies for the surface treatment of micro-channels so as to achieve large slip for maximizing the transport efficiency of fluids through them. Over the last few years, various investigations have also been made to study various flow problems of Newtonian and non-Newtonian fluids with or without the Navier slip boundary condition [14][15][16]. Moreover, accurate prediction for the flow and heat transfer can be achieved by taking into account the variation of these properties with temperature [17].…”
Section: Introductionmentioning
confidence: 99%
“…Liuw et al [13] studied the secondary flow and heat transfer in horizontal channels heated from below. Makinde et al [14] also considered the channel filled with soaked porous medium for temporal stability analysis of hydromagnetic flow. Mounuddin et al [15] studied the steady fluid flow through channel saturated with porous medium with impermeable and thermally insulated bottom.…”
Section: Introductionmentioning
confidence: 99%